MODEL MADRASAH UNGGUL; STRATEGI DAYA SAING LULUSAN DI MTSN 1 BIREUEN - Yunus, Rahma Maulidya (re-JIEM (Research Journal of Islamic Education Management), 2024)
This research was conducted with the aim of analyzing superior madrasah: strategies in increasing the competitiveness of graduates as superior madrasah at MTsN 1 Bireuen. This study uses descriptive designs with a qualitative approach. The results of the study state that the results of SWOT analysis in the implementation of external analysis identify which include several aspects that need to be considered, namely the development of technology and programs that must be developed by the madrasah as well as threats that need to be face. Meanwhile, the internal analysis focuses on the strengths and weaknesses of the madrasah, including the curriculum, facilities and professional education personnel. Based on the SWOT analysis that has been carried out, the strategies that need to be carried out include: 1) development of excellent programs, 2) leaning innovation, 3) madrasah achievements, 4) cooperation network, 5) mastery of technology, 6) education personnel, 7) the personalization approach can be implemented well to achieve excellence in output in the form of competitive graduates from the results of the education process.